Digital generations, but not as we know them. (February 2019) - Fortunati, Leopoldina; Taipale, Sakari; de Luca, Federico
The aim of this article is to see whether or not adolescents were the real leaders of the digital 'revolution' in the 1990s and whether they have sustained or even improved their position in the 2000s. The analysis is based on two surveys carried out in Italy, France, the United Kingdom, Germany, and Spain in 1996 ( N = 6609) and in 2009 ( N = 7255). The results show that the adolescents belonging to the first digital generation in 1996 were the most equipped with new technologies, although not the most intensive users. In 2009, the adolescents lost their position as the leading adopters and lagged behind youth and young adults regarding the use of new technologies and computer skills.